Management model proposal to coordinate quality in the milk production chain - Scalco, Andréa Rossi; Toledo, José Carlos de (Revista Gestão da Produção Operações e Sistemas, 2010)
This article presents a management model for coordinating quality in the milk production chain, which addresses information management on product quality and quality management practices, the identification of quality problems, the elaboration of improvement plans and the monitoring of performance levels in the chain. The model must be adjusted for implementation in each specific milk production and distribution chain, being managed by a coordinating agent, representative and accepted by the chain agents. It was develo- ped from a theoretical reference of quality management areas and production chains, and data raised in case studies conducted at representative companies in the milk chain. The model is structured as a management system, consisting of modules and activities, and follows the control and improvement logic of the PDCA ma- nagement cycle. Keywords: quality management, milk chain, coordination of the quality in production chains.